The Role of Islamic Finance in Enhancing Fiscal Space and Debt Sustainability: Evidence from D8 Countries with a Moderating Role of Institutional Quality - Ijaz, Syeda Tayyaba; Sarwat, Ayesha (International Journal of Islamic Economics and Governance, 2025)
This study investigates the role of Islamic finance in enhancing fiscal space and debt sustainability in D-8 countries, with a special focus on the moderating effect of institutional quality. Using the Driscoll-Kray estimator, the research analyzes key Islamic finance instruments, Sukuk, Takaful, and Islamic banking assets, along with their interactions with institutional quality. The findings reveal that Sukuk alone has a weak and statistically insignificant impact on both fiscal space and debt sustainability. However, when combined with higher institutional quality, Sukuk’s positive effect on fiscal space becomes significant, highlighting the importance of strong governance. Takaful shows a marginally positive influence on fiscal space, but no significant effect on debt sustainability. Nevertheless, its effectiveness improves when institutional quality is high, demonstrating that stronger institutions can enhance Takaful’s role in fiscal development. In contrast, Islamic banking assets negatively and significantly affect both fiscal space and debt sustainability. This negative impact is intensified by higher institutional quality, suggesting that unchecked growth of Islamic banking assets could undermine fiscal stability, especially in well-governed environments. The study also finds that economic openness significantly reduces both fiscal space and debt sustainability, while institutional quality plays a vital role in strengthening debt sustainability. Overall, the results underscore the critical moderating role of institutional quality in amplifying or mitigating the effects of Islamic finance. The study concludes that D-8 countries should focus on enhancing institutional quality to fully leverage the potential of Islamic finance, particularly Sukuk, for sustainable fiscal growth and improved debt management. © 2025 The Author(s). Licensed under CC BY-NC 4.0.